Image based Eye Tracking and Detection for avoiding accidents on Roads: A Review - Snehal B, Meshram; Bodkhe, Sonali (International Journal of Computer Sciences and Engineering, 2014)
This paper aims to provide reliable indications of driver drowsiness describe of detecting early signs of fatigue in drivers and provide method for more security and attention for driver safety problem and to investigate driver mental state related to driver safety.As soon as the driver is falling in symptons of fatigue immediate message will be given to driver.In addition of the advance technology of Surff feature extraction algorithm is also added in the system for correct detection of status of driver.The Fatigue is detected in the system by the image processing method of comparing the images(frames) in the video and by using the human features we are eable to estimate the indirect way of detecting fatigue.The technique also focuses on modes of person when driving vehicle i.e awake, drowsy state or sleepy and sleep state.The system is very efficient to detect the fatigue and control the vehicle.